Causal relationship between multiple types of food intake and myopia: a Mendelian randomization study - Sha-Sha Zhang; Jiao-Jiao Liang; Yun Feng; Xia Hong; Yi-Jia Zhao; Ling Chen; Ping Lin (International Journal of Ophthalmology)
AIM: To investigate the causal relationship between dietary intake and myopia using Mendelian randomization (MR) analysis. METHODS: Genome-wide association study (GWAS) data from the IEU Open GWAS database were utilized to examine associations between myopia and various dietary factors. MR analysis, incorporating both univariable and multivariable approaches, assessed the impact of food intake on myopia risk through five analytical methods, with inverse variance weighted (IVW) serving as the primary reference. Sensitivity analyses, including heterogeneity assessment, horizontal pleiotropy evaluation, and leave-one-out analysis, were conducted to validate the MR findings. RESULTS: Univariable MR analysis identified a causal link between food intake and myopia. Consumption of breaded fish, canned soup, sweet biscuits, and certain fruits correlated with a lower risk of myopia, whereas intake of low-calorie hot chocolate and cereal was associated with an increased risk. Multivariable MR analysis further confirmed that breaded fish consumption exerted a direct protective effect against myopia, particularly when consumed alongside other dietary components. These findings highlight the intricate interplay between specific dietary factors and myopia development, offering valuable insights for further research. CONCLUSION: MR analysis provides evidence supporting a potential causal relationship between breaded fish intake and myopia, underscoring its relevance in targeted myopia prevention strategies.